IMPLEMENTASI PENDIDIKAN KARAKTER MELALUI PROGRAM TAHFIDZ AL-QUR’AN SISWA KELAS III MI NURUL QUR’AN PRESAK TIMUR PAGUTAN MATARAM - Andri Zahid Azzamzami; Farid Zaenudin; Aldin Ahyana; Akmal Ahmad (LPPM Institut Agama Islam Ibrahimy Genteng Banyuwangi, 2022)
Character education is a conscious effort made by educators to students to make children who have good behavior, so that in the formation of character in schools, all must work together in the components (stakeholders) or the education component itself, which involves the curriculum and the teaching and learning process and extracurricular. This study aims to describe the implementation of the Tahfidz Al-Qur'an program character education for third grade students at MI Nurul Qur'an East Presak Pagutan Mataram and to describe the obstacles faced by third grade students in implementing the Tahfidz Al-Qur'an Program at MI Nurul Qur'an Presak Timur Pagutan Mataram, This research uses descriptive qualitative research. Collecting data using interview, observation, and documentation methods. To check the validity of the data using technical triangulation and source triangulation. The results of this study indicate that the process of character education through the tahfidz Al-Qur'an program in class III MI Nurul Qur'an by: a) Character formation through habituation, before reading and memorizing the Qur'an students must: be pure from hadats (ablution) habits like this give birth to a clean character, b) The habit of reading and memorizing the Qur'an before learning gives birth to a disciplined character, c) The teacher requires students to make a deposit every week at least five verses to meet the memorized target that has been set, d) the habit of reading and memorizing the Qur'an gives birth to an honest character.